How to shoe an elk? Teachers' reflections on creating a glocal learning community - Nissinen, Saara; Vartiainen, Henriikka; Vanninen, Petteri; Pöllänen, Sinikka; Kokko, Sirpa (World Scientific, 2025)
This design-based case study aimed to depict how teachers facilitate and experience the design-oriented process of creating and teaching in a glocal learning network. The participants in this case study were volunteer teachers from Finland and theUnited States who designed and implemented glocally-relevant learning projects together with their students. The qualitative data consisted of teachers’ interviews supplemented with project reports and students’ digital artifacts. The deductive content analysis indicates that the enabling of the glocal community and utilizing technology supported the creation of interest-driven inquiries and reciprocal connections with peers and external expertise. While the teachers perceived how the students could develop novel skills and connections in glocally-networked activities, an apparent need to develop the collaboration between the teachers and the global peers was also recognized.
Keywords: technology-enhanced learning; connected learning; design-oriented pedagogy; glocal learning network; case study